A study of the information infrastructure of a Transylvanian village - Littrell, Mary Ann; Nyce, James M.; Straub, Jeanie; Whipple, Mindy (New library world, 2006)
Purpose - To report on the findings obtained through a field study in information infrastructure of rural areas of Romania.Design methodology approach - Researchers interviewed Romanian villagers using the same interpreter regarding a village's information needs and requirements. The village's information infrastructure was also surveyed. Because the literature on information infrastructures has focused primarily on macro issues (those national and international in scale), this project centered on micro (local) issues. A history of Romania's information infrastructure is presented and relevant literature reviewed. This is followed by a discussion of research methods used, and then the findings are presented and analyzed.Findings - The research determined that global information infrastructure (GII) and national information infrastructure (NII) literature is incomplete and needs to give more attention to local and rural (micro level) issues. The findings also raise the question of whether the term equity is "misused" in today's discussions of national and international information infrastructures.Research limitations implications - This was not an exhaustive study. Further studies in the information infrastructure and information requirements of those who live in rural communities are needed in order to fully understand them.Practical implications - Further research will help to identify ways to help improve rural information infrastructures in less developed nation states.Originality value - Little attention in GII NII literature has been given to the information infrastructure of rural or local areas (micro-level issues). Focusing research on this subject will help those who live in areas like these.